2019
DOI: 10.1177/1847979019855504
|View full text |Cite
|
Sign up to set email alerts
|

The impact of project risk management maturity on performance: Complexity as a moderating variable

Abstract: This study examines the utility of project risk management maturity (PRMM) for project-based organizations across different domains. The relationship between organization-level PRMM and firm's performance is studied. Two alternatives of theoretical model are developed on the basis of an extensive literature review. The first model (i.e. traditional model) posits a direct positive relationship between PRMM and organizational performance. The second model suggests that the relation between the two key variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 81 publications
0
13
0
1
Order By: Relevance
“…It is recommended that more attention be placed on organizing risk management according to their effect and influence and more emphasis should be put on communication and project risk management by developing plans for effective communication and risk handling when carrying out projects (Cross, 2019). In the same context, Hartono et al, (2019) examined the impact of project risk management on CPP. The results of their study showed that adopting Project Risk Management Practices has a significant positive impact on project success.…”
Section: The Impact Of Risk Management On Construction Performancementioning
confidence: 99%
“…It is recommended that more attention be placed on organizing risk management according to their effect and influence and more emphasis should be put on communication and project risk management by developing plans for effective communication and risk handling when carrying out projects (Cross, 2019). In the same context, Hartono et al, (2019) examined the impact of project risk management on CPP. The results of their study showed that adopting Project Risk Management Practices has a significant positive impact on project success.…”
Section: The Impact Of Risk Management On Construction Performancementioning
confidence: 99%
“…This concept is adopted from the project risk term, which is defined as “ an uncertain event or condition that, if it occurs, has a positive or a negative effect on a project objective .” 19 From normative rational theory, risk in project could be positive (opportunities) or negative (threats). 169,170,171,172,173 Positive challenges are associated with “opportunities” that could be gained from complexity aspects, and negative challenges are related with the “loss” from complexity condition. For instance, due to limited experience, several megaproject teams or stakeholders in developing countries often under uncertain conditions for structural aspect in the technology are to be applied.…”
Section: Resultsmentioning
confidence: 99%
“…The level of risk management maturity has a great impact on the companies' financial health (Mohammed & Knapkova, 2016;Otero González et al, 2020). In addition, the level of risk management maturity also may affect the company's performance (Ekwere, 2016;Hartono, Wijaya, & Arini, 2019).…”
Section: Introductionmentioning
confidence: 99%